2002
DOI: 10.1093/hmg/11.18.2165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a major modifier locus for polycystic kidney disease (Modpkdr1) in the Han:SPRD(cy/+) rat in a region conserved with a mouse modifier locus for Alport syndrome

Abstract: The genetic analysis of rodent disease models provides a powerful tool to investigate how modifier loci cause variation in the phenotypic expression of a disease. In order to test the existence of modifier loci influencing polycystic kidney disease (PKD) phenotypes, we derived a backcross between PKD susceptible Han:SPRD(cy/+) and control Brown Norway (BN) rats, and performed a whole-genome scan in 182 PKD affected hybrids showing different grades of disease severity. The genetic dissection of PKD in the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The identification of the mutation that is likely to cause renal cyst development in the PKD/Mhm(cy/ϩ) rat in a novel gene encoding SamCystin provides new opportunities for further dissecting mechanisms that control cystogenesis and modulate PKD severity (11). Both this novel gene and genes that encode proteins that interact with SamCystin call for large-scale genetic and functional studies in human PKD that may have significant implications for the clinical classification of cystic kidney diseases and the development of novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of the mutation that is likely to cause renal cyst development in the PKD/Mhm(cy/ϩ) rat in a novel gene encoding SamCystin provides new opportunities for further dissecting mechanisms that control cystogenesis and modulate PKD severity (11). Both this novel gene and genes that encode proteins that interact with SamCystin call for large-scale genetic and functional studies in human PKD that may have significant implications for the clinical classification of cystic kidney diseases and the development of novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort of 742 first-backcross (BC1) rats was derived from affected F1(cy/ϩ) rats that were mated to BN rats as described previously (11). The BN rat was preferred to other inbred rat strains because of the high level of allele variation observed between BN and PKD/ Mhm(cy/ϩ) strains, which facilitates the detection of recombinant hybrids in the BC1 cohort and therefore increases efficiency of positional cloning the disease gene.…”
Section: Animals and Phenotype Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models such as the MWF rat represent valuable models to substitute the investigation of the polygenetic basis of common forms of chronic proteinuric nephropathies (1,4). Indeed, susceptibility loci identified in rodent models have been shown to be predictive for human genetic studies using the comparative genomic approach (26,27). Such susceptibility loci may provide target regions for subsequent studies using single nucleotide polymorphisms and linkage disequilibrium mapping in association studies in human patient populations (28 -30).…”
Section: Discussionmentioning
confidence: 99%
“…In both sexes, renal cystic disease is modulated by genetic background. Genetic mapping studies have identified a rat Chr 8 locus designated Modpkdr1, which exerts a main effect on renal disease severity (10).…”
Section: Rat Pkd Modelsmentioning
confidence: 99%